Assessment of the occupational health and food safety risks associated with the traditional slaughter and consumption of goats in Gauteng, South Africa - Qekwana, D.N.; McCrindle, C.M.E.; Oguttu, J.W.; Grace, Delia (MDPI, 2017)
Background: This study assessed the occupational health and food safety risks associated with the traditional slaughter of goats and the consumption of such meat in Tshwane, South Africa. Methods: A convenience sample of 105 respondents agreed to be interviewed using structured questionnaires. Results: A high proportion (62.64%) of practitioners admitted to not wearing protective clothing during slaughter. Slaughtering was mainly carried out by males (99%) with experience (62.2%). Forty-four percent of practitioners only changed the clothes they wore while slaughtering when they got home. During the actual slaughter, up to seven people may be involved. The majority (58.9%) of slaughters occurred early in the morning and none of the goats were stunned first. In 77.5% of cases, the health status of the persons who performed the slaughtering was not known. The majority (57.3%) of the slaughters were performed on a corrugated iron roof sheet (zinc plate). In 83.3% of the cases, the carcass was hung up to facilitate bleeding, flaying, and evisceration. Meat inspection was not practiced by any of the respondents. Throughout the slaughter process, the majority used the same knife (84.3) and 84.7% only cleaned the knife when it became soiled. A total of 52.0% of the respondents processed the carcass and cooked the meat immediately. The majority (80.0%) consumed the meat within 30 min of cooking. Conclusions: Men are at a higher risk of occupational health hazards associated with traditional slaughter, which can be transferred to their households. Unhygienic methods of processing and the lack of any form of post-mortem examination increase the risk of food-borne illness following the consumption of such meat.